Skin closure using simple interrupted and continuous subcuticular nylon sutures: a comparison of results - Loo, J.T.; Md Razif, M.A. (Faculty of Medicine, University of Malaya, 2003)
Skin closure using simple interrupted nylon sutures was compared with closure using subcuticular nylon sutures in 80 consecutive patients undergoing semiemergency surgery, involving open reduction and internal fixation of either the forearm bones or femur. The simple interrupted technique was shown to be slower than the subcuticular technique with higher early postoperative wound complication rate. It may use an extra packet of sutures particularly if the average wound length is 19.8 cm. There is, however, no statistical difference demonstrated for the late scar complaints or subjective and objective scoring of cosmetic outcomes six months after the surgery.